Elbow replacement for elective elbow conditions. Issue 4 (August 2016) - Vollans, Sam; Limb, David
Abstract: The outcomes of total elbow replacement are implicitly linked to performing the surgery for the correct indications in good candidates. With this in mind, we provide an overview of elbow replacement to enable the reader to confidently assess and investigate a patient and consider elbow replacement as an option for the correct indication. In addition, we outline the operative technique of total elbow replacement and some of the advances and challenges that lie ahead in revision elbow replacement.